Increased plasma sCXCL16 levels may have a relationship with Th1/Th2 imbalance in primary immune thrombocytopenia. (November 2017) - Hao, Yating; Li, Yang; Li, Huiyuan; Lyu, Mingen; Zhang, Donglei; Fu, Rongfeng; Guan, Yue; Wang, Shixuan; Sun, Boyang; Dou, Xueqing; Zhang, Lei; Yang, Renchi
Highlights: Plasma circulating sCXCL16 levels were increased and positively associated with IFN-γ/IL-4 ratio in ITP. The receptor, CXCR6 mRNA and protein expression were increased. Effective therapy could correct the abnormity of CXCL16 and CXCR6 in ITP. Abstract: Primary immune thrombocytopenia (ITP) is a disease of autoimmunity in which there are Th1/Th2 imbalance and disordered cytokine profiles. CXC chemokine ligand 16 (CXCL16) was proved to implicate in some autoimmune diseases. Our research aimed to determine plasma soluble CXCL16 (sCXCL16) levels and its effects in ITP. We used ELISA to measure plasma sCXCL16, IFN–γ and IL-4 and flow cytometry to determine expression of CXCR6 on lymphocyte subsets. We used real-time PCR to detect the CXCL16 and CXCR6 mRNA expression. Additionally, plasma sCXCL16, CXCL16 and CXCR6 mRNA levels of 8 patients were monitored before and after treatment. We found that patients with active ITP had higher circulating sCXCL16 in plasma than healthy controls and patients in remission. Meanwhile, negative relationships between sCXCL16 and platelet count, IL-4 and positive relationships between sCXCL16 and IFN-γ, IFN-γ/IL-4 ratio were observed. Besides, expression of CXCR6 on lymphocyte subsets and mRNA levels of CXCL16 and CXCR6 were all increased in active ITP. Additionally, plasma sCXCL16 and IFN-γ levels and CXCR6 mRNA expression were down-regulated after effective treatment compared with those before treatment. Thus, increased plasma sCXCL16 might be implicated in the pathogenesis of ITP and have a relationship with Th1/Th2 imbalance.